Proposta de implantação de fossa biodigestora adaptada para ambiente de várzea para a sede do projeto social Sorrisos do Rio - PINA, Camila Silva (2024)
This document presents a proposal for the implementation of an adapted biodigester septic tank system in the várzea environment for the headquarters of the social project "Sorrisos dos Rios". The project aims to provide basic healthcare services to vulnerable riverine communities in the metropolitan region of Belém, Pará, Brazil. The proposal highlights the challenges faced in the state of Pará regarding public health services and basic sanitation in remote areas. It emphasizes the importance of sustainable solutions and introduces the concept of a biodigester septic tank system, which can treat effluents and contribute to environmental preservation. The document discusses the methodology of the project, including technical visits, data collection, and the proposed intervention. It also presents successful case studies of biodigester septic tank implementations in rural areas in Brazil. The document concludes by emphasizing the potential of the biodigester septic tank system to improve the quality of life for riverine communities and suggests future work to expand the implementation of these technologies in rural areas.